Aplikasi Pembelajaran Kriptograpi berbasis Mobile menggunakan Computer Assisted Instruction - Hutahaean, Harvei Desmon; Hasugian, Paska Marto (LPPM UNIKA Santo Thomas Medan, 2019)
The source of science is still dominated by books, although with the internet students get information with diverse scientific fields, but actually the information comes from material in the book. To be able to master a material from a book, students must first be able to read and understand well. Nowadays software is growing very rapidly. The world of education has also used software to create interactive learning application methods with multimedia concepts. This can help overcome, the level of difficulty experienced by students, in order to be able to attract student learning interest, so that it can automatically improve the learning process to be more active and effective. Actually this method has been widely used and has good benefits in learning. As for the achievements of this study to assist students in learning and understanding the learning of data security techniques, this is a solution in several learning problems, namely an explanation that is too fast, a conducive atmosphere, time, learning media and student interest.